2022
DOI: 10.4103/jfmpc.jfmpc_2437_21
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous vitamin C in management of moderate and severe COVID-19: A double blind randomized placebo controlled trial

Abstract: Aim: To study the efficacy of intravenous vitamin C in management of moderate and severe COVID-19. Objective: To determine the efficacy of intravenous vitamin C in reducing in-hospital mortality in moderate and severe cases of COVID-19. Design: Parallel, double-blinded randomized controlled trial with placebo. Ethical clearance was obtained from the institutional ethics committee, AIIMS Patna. The trial was registered with the Clinical Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Eight studies were excluded either due to observational study design or reported no mortality events. In total, we included eleven randomized controlled trials (Beigmohammadi et al 2021 ; Cao et al 2020 ; JamaliMoghadamSiahkali et al 2021 ; Kumar et al 2022 ; Kumari et al 2020 ; Labbani-Motlagh et al 2022 ; Leal-Martínez et al 2022 ; Majidi et al 2021 ; Tehrani et al 2022 ; Thomas et al 2021 ; Zhang et al 2021 ) in our systematic review and meta-analysis, with 445 patients randomized to receive vitamin C and 494 patients randomized to receive comparative interventions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies were excluded either due to observational study design or reported no mortality events. In total, we included eleven randomized controlled trials (Beigmohammadi et al 2021 ; Cao et al 2020 ; JamaliMoghadamSiahkali et al 2021 ; Kumar et al 2022 ; Kumari et al 2020 ; Labbani-Motlagh et al 2022 ; Leal-Martínez et al 2022 ; Majidi et al 2021 ; Tehrani et al 2022 ; Thomas et al 2021 ; Zhang et al 2021 ) in our systematic review and meta-analysis, with 445 patients randomized to receive vitamin C and 494 patients randomized to receive comparative interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The regimen of vitamin C in the intervention group differed across the included trials. Most of the included trials (n = 6) (Beigmohammadi et al 2021 ; JamaliMoghadamSiahkali et al 2021 ; Kumar et al 2022 ; Labbani-Motlagh et al 2022 ; Tehrani et al 2022 ; Zhang et al 2021 ) administered vitamin C intravenously at a fixed non–weight-based dose ranging from 2 to 24 g daily for a duration of 4 to 7 days. One trial (Kumari et al 2020 ) administered vitamin C intravenously at a weight-based dose of 50 mg/kg daily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations